2023
DOI: 10.1177/20539517231176228
|View full text |Cite
|
Sign up to set email alerts
|

Algorithmic probing: Prompting offensive Google results and their moderation

Abstract: Google results have been scrutinized over the years for what they privilege, be it the surface web, the powerful, optimized webpages, the personalized and/or their own properties. For some time now, another type of Google returns also has been the source of attention: the offensive result. The following revisits a selection of offensive and other problematic results found by journalists and researchers alike. In a technique termed ‘algorithmic probing’, the prompting queries are re-run to study what has come o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…On the contrary, with the integration of more and more data-driven algorithms, analytics, and artificial intelligence (AI) in both commercial and public domains, algorithmic bias and asymmetries continue to lead to inequalities and social disadvantages (Allhutter et al, 2020; Benjamin, 2019; Eubanks, 2018). Following this line of research, three contributions to the present special issue explicitly focus on search engine bias and discrimination in the context of extreme-right dynamics of exclusion (Norocel and Lewandowski, 2023), the ethical dimensions of Google Autocomplete (Graham, 2023), and Google's balancing of suggesting and moderating offensive content (Rogers, 2023).…”
Section: From Pagerank To “Assetization” Of Audiences: Articulating G...mentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, with the integration of more and more data-driven algorithms, analytics, and artificial intelligence (AI) in both commercial and public domains, algorithmic bias and asymmetries continue to lead to inequalities and social disadvantages (Allhutter et al, 2020; Benjamin, 2019; Eubanks, 2018). Following this line of research, three contributions to the present special issue explicitly focus on search engine bias and discrimination in the context of extreme-right dynamics of exclusion (Norocel and Lewandowski, 2023), the ethical dimensions of Google Autocomplete (Graham, 2023), and Google's balancing of suggesting and moderating offensive content (Rogers, 2023).…”
Section: From Pagerank To “Assetization” Of Audiences: Articulating G...mentioning
confidence: 99%
“…This special issue collects five original research articles (Haider and Rödl, 2023; Mager, 2023; Norocel and Lewandowski, 2023; Ridgway, 2023; Rogers, 2023) and two invited commentaries (Graham, 2023; Rieder, 2022), all of which are devoted to the state of Google critique and intervention by engaging critically with its study as well as prospecting for alternatives. Three contributions focus on search engine bias and discrimination in the context of right-wing extremism (Norocel and Lewandowski, 2023), Google Autocomplete (Graham, 2023), and content moderation (Rogers, 2023).…”
Section: Contemporary Google Studies: Special Issue Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recently published special issue of Big Data and Society (Mager et al, 2023) focuses on "The State of Google Critique and Intervention." The topics covered in this special issue will sound familiar to information science researchers: Methods for investigating offensive search results (Rogers, 2023), data voids and racism (Norocel & Lewandowski, 2023), how Google creates ignorances on the climate crisis (Haider & Rödl, 2023), ethical concerns associated with Google's auto-complete function (Graham, 2023b), European alternatives to Google (Mager, 2023), as well as conceptual development to nuance the critique "big tech" (Rieder, 2022). In the same year a special issue of Social Media and Society appeared under the title "Semantic Media."…”
Section: Renewed Interest In Search Engine Researchmentioning
confidence: 99%
“…The renewed interest in search engine studies is also shown by the publication of special issues in journals, like this one. A recently published special issue of Big Data and Society (Mager et al, 2023) focuses on “The State of Google Critique and Intervention.” The topics covered in this special issue will sound familiar to information science researchers: Methods for investigating offensive search results (Rogers, 2023), data voids and racism (Norocel & Lewandowski, 2023), how Google creates ignorances on the climate crisis (Haider & Rödl, 2023), ethical concerns associated with Google's auto‐complete function (Graham, 2023b), European alternatives to Google (Mager, 2023), as well as conceptual development to nuance the critique “big tech” (Rieder, 2022). In the same year a special issue of Social Media and Society (Iliadis & Ford, 2023) appeared under the title “Semantic Media.” The majority of contributions in this issue concern, in one way or another, search processes, search engines and address their various implications in how meaning and knowledge emerge in society (Dobreski et al, 2023; Ford & Iliadis, 2023; Giomelakis, 2023; Jobin, 2023; Tripodi & Dave, 2023).…”
Section: Renewed Interest In Search Engine Researchmentioning
confidence: 99%